Prairie Protector: student development of systems thinking habits in the context of agroecosystems - Ingram, Erin; Keshwani, Jenny (Frontiers in Education, 2023)
Introduction The Great Plains ecosystem offers an opportunity for young people to gain knowledge about intricate systems through practical learning. The spread of woody plants into grasslands, known as the “Green Glacier,” poses a risk to biodiversity and animal production. Although effective management strategies exist, some land managers are reluctant to use them. It is critical to cultivate a scientifically literate population that can think systematically and make informed decisions based on STEM principles to address such complex agroecosystem problems. Methods In this study, semi-structured focus group discussions with high school students were analyzed to determine whether Prairie Protector, an educational game, and its associated resources led to evidence of systems thinking habits in student conversation. Results Analysis of the focus group transcripts revealed that the students developed systems thinking habits through their experience playing Prairie Protector while developing empathy for land managers and others involved in the Great Plains agroecosystem. In general, students found the game enjoyable and a useful tool for learning about agroecosystems, conservation land management, and the spread of invasive species. Discussion Analysis of the student statements led to the development of a guiding framework to assess and analyze students development of systems thinking habits that could be used to scaffold student learning experiences to explore, understand, and interact with complex systems. Providing simulated environments for students to interact with complex systems should be explored in additional scenarios to support student development of systems thinking skills.